2000
DOI: 10.1542/peds.105.3.496
|View full text |Cite
|
Sign up to set email alerts
|

Pediatricians' Attitudes, Beliefs, and Practices Regarding Clinical Practice Guidelines: A National Survey

Abstract: Most general pediatricians use practice guidelines, but no specific guidelines, except those for asthma, are used by >27% of pediatricians. The results of this study suggest that practice guidelines are most likely to be followed if they are simple, flexible, rigorously tested, not used punitively, and are motivated by desires to improve quality, not reduce costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
151
1
4

Year Published

2001
2001
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 194 publications
(162 citation statements)
references
References 11 publications
6
151
1
4
Order By: Relevance
“…Children in their study who were seen by private practice physicians were more likely to receive appropriate care based on practice guidelines than those treated in public settings. The notion that practice type is associated with the delivery of care deemed appropriate by national guidelines has also been reported by Flores et al, 24 who found that clinical practice guideline use was more common among pediatricians who practiced in HMOs than in other settings.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…Children in their study who were seen by private practice physicians were more likely to receive appropriate care based on practice guidelines than those treated in public settings. The notion that practice type is associated with the delivery of care deemed appropriate by national guidelines has also been reported by Flores et al, 24 who found that clinical practice guideline use was more common among pediatricians who practiced in HMOs than in other settings.…”
mentioning
confidence: 61%
“…Rust et al 29 reported that community health centers are generally unable to provide quality asthma care to traditionally underserved populations because of a lack of adequate resources. Flores et al 24 reported that adherence to practice guidelines was more common in HMOs than in other settings. Other studies have identified provider factors such as imperfect pediatric conformity to clinical practice guidelines, particularly in community-or hospital-based clinics.…”
Section: Discussionmentioning
confidence: 99%
“…6,7 These findings parallel results of other investigations regarding clinician awareness and adherence to guideline recommendations in all specialties, including pediatrics. 8 Clearly, for clinical practice guidelines to be effective, more must be done to improve their dissemination and implementation.…”
Section: Introductionmentioning
confidence: 99%
“…In a survey of general pediatricians, most failed to use guidelines despite agreeing that guidelines improve outcomes. 37 High-quality health care should be, at a minimum, safe and effective (the Institute of Medicine [IOM] has also recommended that care be patient-centered, timely, equitable, and efficient). 38 Although information on the quality of child health services is limited, evidence reveals large gaps between what should occur and what actually does.…”
Section: Voltage Drop 3: Access To Covered Services and Providersmentioning
confidence: 99%